Non-aqueous electrolyte secondary battery

By reducing the electrode density of nonaqueous electrolyte secondary battery and appropriate compression force, the problems of battery capacity retention and gas generation are solved, and higher capacity retention and lower gas generation are achieved.

JP7658343B2Active Publication Date: 2025-04-08TOYOTA JIDOSHA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022118453
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-07-26
Publication Date
2025-04-08
Estimated Expiration
2042-07-26

AI Technical Summary

Technical Problem

When the existing nonaqueous electrolyte secondary batteries increase the battery capacity, the electron and ion conductivity decreases, resulting in an increase in electrode impedance and a decrease in capacity retention. At the same time, the internal pressure of high-capacity batteries increases during the initial charging and discharge, resulting in gas generation and affecting battery characteristics.

Method used

By reducing the electrode density and applying appropriate compression force, the temperature and gas generation of the electrode body are controlled, ensuring that the amount of pores in the electrode body is sufficient to store sufficient electrolytes, thereby increasing capacity retention and reducing gas generation.

Benefits of technology

It effectively improves the battery capacity retention rate, reduces gas generation, and improves the internal pressure and characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658343000003
    Figure 0007658343000003
  • Figure 0007658343000004
    Figure 0007658343000004
  • Figure 0007658343000005
    Figure 0007658343000005
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte secondary battery, in which both of suppression of decline in capacity retention rate and reduction in gas yield are achieved.SOLUTION: A nonaqueous electrolyte secondary battery includes an electrolytic solution and an electrode body in which a positive electrode and a negative electrode are stacked via a separator. The positive electrode includes a positive electrode current collector foil and a positive electrode active material layer, and the negative electrode includes a negative electrode current collector foil and a negative electrode active material layer. The basis weight of the positive electrode active material layer exceeds 25 mg / cm2, and the density of the positive electrode is 1.9 g / cm3 or more and 2.1 g / cm3 or less. The basis weight of the negative electrode active material layer exceeds 10 mg / cm2, and the density of the negative electrode is 1.3 g / cm3 or more and less than 1.5 g / cm3. A confining pressure of 0.1 MPa or more and 1.0 MPa or less is applied to the electrode body in a stack direction.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] Patent Document 1 (JP 2018-106868 A) discloses that in a nonaqueous electrolyte secondary battery including a wound electrode body, the curved portion that forms the curved exterior shape of the wound electrode body is restrained with a pressure of 0.6 MPa or more. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-106868 A Summary of the Invention [Problem to be solved by the invention]

[0004] There is a demand for a non-aqueous electrolyte secondary battery with a higher capacity. In order to achieve a higher capacity, the weight of the electrode is increased, the density of the electrode is increased, and the like. However, when the weight of the electrode is increased, the electronic conductivity and ionic conductivity are decreased, so that the resistance of the electrode increases and the capacity retention rate may decrease. In addition, when the density of the electrode is increased, the pore volume of the electrode is decreased, so that the electrolyte solution held in the electrode is decreased, and the electrode may deteriorate or the capacity retention rate may decrease.

[0005] In addition, in non-aqueous electrolyte secondary batteries, gas is generated on the electrode surface during initial charging due to decomposition of moisture contained in the electrolyte and battery components. The generation of gas increases the internal pressure of the battery, which causes defects in battery characteristics. In particular, in high-capacity non-aqueous electrolyte secondary batteries, the amount of heat generated increases, causing the temperature of the electrodes to rise, which tends to result in a large amount of gas generation.

[0006] Therefore, an object of the present disclosure is to provide a nonaqueous electrolyte secondary battery that achieves both suppression of a decrease in capacity retention rate and a reduction in the amount of gas generation. [Means for solving the problem]

[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.

[0008] [1] A nonaqueous electrolyte secondary battery including an electrode assembly formed by laminating a positive electrode and a negative electrode with a separator interposed therebetween, and an electrolyte solution, The positive electrode includes a positive electrode current collector foil and a positive electrode active material layer, the negative electrode includes a negative electrode current collector foil and a negative electrode active material layer, The weight of the positive electrode active material layer is 25 mg / cm 2 It exceeds The density of the positive electrode is 1.9 g / cm 3 More than 2.1g / cm 3 is as follows: The negative electrode active material layer has a coating weight of 10 mg / cm 2 It exceeds The density of the negative electrode is 1.3 g / cm 3 More than 1.5g / cm 3 is less than a confining pressure of 0.1 MPa or more and 1.0 MPa or less is applied to the electrode assembly in a stacking direction.

[0009] Even if the electrode has a high basis weight, the electrode temperature rise is suppressed by lowering the electrode density and the confining pressure, and the amount of gas generation is expected to be reduced. In addition, since the electrode density is low, the pore volume in the electrode increases. Therefore, the amount of electrolyte held in the electrode increases, and the capacity retention rate is expected to improve.

[0010] [2] The positive electrode active material layer contains lithium iron phosphate, The nonaqueous electrolyte secondary battery according to [1], wherein the average particle size of the secondary particles of the lithium iron phosphate is 1 μm or more and 30 μm or less.

[0011] [3] A nonaqueous electrolyte secondary battery including an electrode assembly formed by laminating a positive electrode and a negative electrode with a separator interposed therebetween, and an electrolyte solution, The positive electrode includes a positive electrode current collector foil and a positive electrode active material layer, the negative electrode includes a negative electrode current collector foil and a negative electrode active material layer, The weight of the positive electrode active material layer is 28 mg / cm 2 More than 35mg / cm 2 is as follows: The density of the positive electrode is 1.9 g / cm 3 More than 2.1g / cm 3 is as follows: The weight of the negative electrode active material layer is 15 mg / cm 2 More than 20mg / cm 2 is as follows: The density of the negative electrode is 1.35 g / cm 3 More than 1.5g / cm 3 is less than The electrode body is applied with a confining pressure of 0.2 MPa or more and 0.7 MPa or less in the stacking direction, The positive electrode active material layer contains lithium iron phosphate, The lithium iron phosphate secondary particles have an average particle size of 1 μm or more and 30 μm or less. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram showing an example of a nonaqueous electrolyte secondary battery according to the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of the electrode body of the present embodiment. [Diagram 3] FIG. 3 is a graph showing the capacity retention rates after cycle testing in Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 5. [Figure 4] FIG. 4 is a graph showing the amount of gas generated versus the capacity retention rate after cycle testing in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure. In this disclosure, the nonaqueous electrolyte secondary battery will be simply referred to as "battery".

[0014] <Nonaqueous electrolyte secondary battery> 1 is a schematic diagram showing an example of a nonaqueous electrolyte secondary battery of this embodiment. The battery 100 includes a case 90 and a binding member (not shown). The case 90 has any shape. The case 90 may be, for example, rectangular or cylindrical. The case 90 may be, for example, made of metal, or may be a pouch made of an aluminum (Al) laminate film. The case 90 may be provided with a positive electrode terminal 91 and a negative electrode terminal 92.

[0015] The case 90 houses the electrode assembly 50 and an electrolyte. The electrolyte is impregnated in the electrode assembly 50. The electrode assembly 50 is connected to a positive electrode terminal 91 and a negative electrode terminal 92.

[0016] FIG. 2 is a schematic diagram showing an example of the electrode body of this embodiment. The electrode body 50 is, for example, a wound type. The electrode body 50 includes a positive electrode 20, a separator 40, and a negative electrode 30. The positive electrode 20, the separator 40, and the negative electrode 30 are all strip-shaped sheets. The electrode body 50 can be formed by stacking the positive electrode 20 and the negative electrode 30 with the separator 40 interposed therebetween and further winding them in a spiral shape. Two separators 40 may be used. After winding, the electrode body 50 may be formed into a flat shape.

[0017] The electrode body 50 is, for example, a laminate type. The electrode body 50 is formed by laminating the positive electrode 20 and the negative electrode 30 with the separator 40 interposed therebetween. The electrode body 50 may have any laminate structure as long as it includes at least one layer each of the positive electrode 20, the separator 40, and the negative electrode 30. For example, the electrode body 50 may be formed by laminating the positive electrode 20, the separator 40, the negative electrode 30, the separator 40, and the positive electrode 20 in this order.

[0018] 《Positive electrode》 The positive electrode 20 includes a positive electrode current collector foil and a positive electrode active material layer. The positive electrode current collector foil may include, for example, an aluminum (Al) foil.

[0019] positive electrode active material layer The density of is 1.9g / cm 3 More than 2.1g / cm 3 The following is the positive electrode active material layer The density is 1.9g / cm 3 If it is less than this, the electronic conductivity may decrease. active material layer The density is 2.1g / cm 3 If it exceeds active material layer Since the pore volume of the battery is reduced and the ionic conductivity is decreased, there is a risk of the capacity retention rate being reduced.

[0020] The positive electrode active material layer includes a positive electrode active material. The positive electrode active material is, for example, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, or lithium nickel cobalt manganese oxide (NCM) (for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 The battery may contain at least one selected from the group consisting of lithium iron phosphate (LFP), etc. From the viewpoints of durability and safety, LFP is preferred.

[0021] The positive electrode active material may be primary particles or secondary particles. The secondary particles are an aggregate of primary particles. The average particle size (D50) of the primary particles may be, for example, 0.01 μm or more and 3 μm or less, or 0.1 μm or more and 1 μm or less. The D50 of the secondary particles may be, for example, 1 μm or more and 30 μm or less, or 2 μm or more and 10 μm or less. From the viewpoint of durability and battery characteristics, it is preferable that the D50 of the primary particles and the secondary particles is small. Note that D50 indicates the particle size at which the cumulative frequency from the small particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.

[0022] The weight of the positive electrode active material layer is 25 mg / cm 2 The weight of the positive electrode active material layer is more than 25 mg / cm 2 In the following cases, it is difficult to increase the capacity of the battery. 2 From the viewpoint of increasing the capacity, it is preferable to increase the basis weight of the positive electrode active material layer. 2 or less, 30 mg / cm 2 It may be the following.

[0023] The positive electrode active material layer may further include, for example, a conductive material, a binder, etc. The conductive material may include, for example, acetylene black (AB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT), etc. The binder may include, for example, polyvinylidene fluoride (PVdF), etc. The blending amount of the conductive material and the binder may be, for example, 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the positive electrode active material.

[0024] 《Negative electrode》 The negative electrode 30 includes a negative electrode current collector foil and a negative electrode active material layer. The negative electrode current collector foil may include, for example, a copper (Cu) foil.

[0025] negative electrode active material layer The density of is 1.3g / cm 3 More than 1.5g / cm3 Less than 100%. active material layer The density is 1.3g / cm 3 If less than 100%, the negative electrode active material layer The pore volume of the negative electrode decreases, and the ionic conductivity decreases, which may result in a decrease in the capacity retention rate. active material layer The density is 1.5g / cm 3 In the above cases, the electronic conductivity may decrease.

[0026] The negative electrode active material layer includes a negative electrode active material. The negative electrode active material may include, for example, at least one selected from the group consisting of graphite, soft carbon, hard carbon, silicon, and silicon oxide.

[0027] The weight of the negative electrode active material layer is 10 mg / cm 2 The coating weight of the negative electrode active material layer is more than 10 mg / cm 2 In the following cases, it is difficult to increase the capacity of the battery. 2 From the viewpoint of increasing the capacity, it is preferable to increase the coating weight of the negative electrode active material layer. 2 or less, 17 mg / cm 2 It may be the following.

[0028] The negative electrode active material layer may further include, for example, a thickener, a binder, etc. The thickener may include, for example, carboxymethyl cellulose (CMC), methyl cellulose (MC), etc. The binder may include, for example, styrene butadiene rubber (SBR), PVdF, etc. The blending amount of the thickener and the binder may be, for example, 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the negative electrode active material.

[0029] <Separator> The separator 40 is porous. The separator 40 is permeable to an electrolyte. The separator 40 separates the positive electrode 20 and the negative electrode 30. The separator 40 is electrically insulating. The separator 40 may contain, for example, a polyolefin resin such as polyethylene (PE) or polypropylene (PP). The separator 40 may have, for example, a single-layer structure or a multi-layer structure. The separator 40 may be substantially composed of a PE layer, or may be formed by laminating a PP layer, a PE layer, and a PP layer in this order. For example, a heat-resistant layer may be formed on the surface of the separator 40.

[0030] 《Electrolyte》 The electrolyte includes a solvent and a Li salt. The solvent is aprotic. The solvent may include any component. For example, the solvent may include at least one selected from the group consisting of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC).

[0031] The Li salt is a supporting electrolyte. The Li salt is dissolved in a solvent. The Li salt is, for example, LiPF 6 and LiBF 4 The Li salt may contain at least one selected from the group consisting of: The Li salt may have a molar concentration of, for example, 0.5 mol / L or more and 2.0 mol / L or less.

[0032] The electrolytic solution may further contain an arbitrary additive. For example, the electrolytic solution may contain 0.01 to 5 mass % of the additive. For example, the additive may contain at least one selected from the group consisting of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and the like.

[0033] 《Bind》 The restraining member applies pressure (restraining pressure) to the electrode assembly 50. The restraining pressure is applied in the stacking direction of the electrode assembly 50. The restraining member may be disposed outside the case 90. The restraining member may apply pressure to the electrode assembly 50 via the case 90.

[0034] The confining pressure is 0.1 MPa or more and 1.0 MPa or less. If the confining pressure is less than 0.1 MPa, the capacity retention rate may decrease because the confining pressure is too low. If the confining pressure exceeds 1.0 MPa, the temperature of the electrode body 50 may increase, and the amount of gas generated may increase. The confining pressure is preferably 0.2 MPa or more and 0.7 MPa or less.

[0035] 《Capacity ratio》 The ratio of the negative electrode capacity to the positive electrode capacity (hereinafter also referred to as "opposite capacity ratio") exceeds 1.1. If the opposite capacity ratio is 1.1 or less, Li that cannot be inserted into the negative electrode 30 grows into dendrites, which may increase the irreversible capacity and reduce the capacity retention rate. The opposite capacity ratio may be 1.3 or more. The negative electrode capacity is calculated by multiplying the total mass of the negative electrode active material contained in the negative electrode 30 by the specific capacity of the negative electrode active material. The positive electrode capacity is calculated by multiplying the total mass of the positive electrode active material contained in the positive electrode 20 by the specific capacity of the positive electrode active material. EXAMPLES

[0036] The present embodiment will be described below using examples, but the present embodiment is not limited to these.

[0037] Example 1 (positive electrode) An Al foil (thickness: 15 μm) was prepared as the positive electrode current collector foil, LFP (92.86 mass%) as the positive electrode active material, AB (2.78 mass%) and VGCF (2.77 mass%) as the conductive material, and PVdF (1.59 mass%) as the binder. The positive electrode active material, the conductive material, and the binder were mixed to prepare a positive electrode powder. The positive electrode powder was applied to the surface of the positive electrode current collector foil to form a positive electrode active material layer. The positive electrode was manufactured by compressing the positive electrode active material layer and the positive electrode current collector foil with a roll press machine equipped with two rotating rolls. At this time, the gap between the two rolls was adjusted so that the desired basis weight and density were obtained. The basis weight and density were the values ​​shown in Table 1. In addition, secondary particles were used for LFP, and D50 was within the range of 1 to 30 μm. Moreover, in Examples 2 to 7, Comparative Examples 1 to 9, and Reference Examples 1 to 5 described later, the basis weight and density were similarly measured and the values ​​shown in Table 1 were obtained.

[0038] (Negative electrode) A Cu foil (thickness: 10 μm) was prepared as the negative electrode current collector foil, graphite (98 mass%) as the negative electrode active material, CMC (1 mass%) as the thickener, and SBR (1 mass%) as the binder. The negative electrode powder was prepared by mixing the negative electrode active material, the thickener, and the binder. The negative electrode powder was applied to the surface of the negative electrode current collector foil to form a negative electrode active material layer. The negative electrode was manufactured by compressing the negative electrode active material layer and the negative electrode current collector foil with a roll press machine equipped with two rotating rolls. At this time, the gap between the two rolls was adjusted so as to obtain the desired basis weight and density. The basis weight and density were the values ​​shown in Table 1. In addition, in Examples 2 to 7, Comparative Examples 1 to 9, and Reference Examples 1 to 5 described later, the basis weight and density were similarly measured, and the values ​​shown in Table 1 were obtained.

[0039] (Separator) A separator (porous membrane) having a thickness of 15 to 17 μm was prepared. This separator has a three-layer structure. The three-layer structure is formed by laminating a PP porous layer, a PE porous layer, and a PP porous layer in this order.

[0040] (electrolyte) A mixed solvent was prepared by mixing EC, DMC, and EMC. The mixing ratio (volume ratio) of EC, DMC, and EMC was 3:4:3. The solvent contained LiPF 6 The electrolyte was prepared by dissolving LiPF 6 was dissolved in the electrolyte to a concentration of 1.0 to 1.2 mol / L.

[0041] (Nonaqueous electrolyte secondary battery) A positive electrode, a separator, and a negative electrode were laminated in this order to form an electrode body. A pouch made of a laminate film was prepared as a case. The electrode body was housed in the case. An electrolyte was injected into the case. After the electrolyte was injected, the case was sealed. A restraining member was prepared. The restraining member was attached to the outside of the case so as to achieve the restraining pressure shown in Table 1. From the above, the battery of Example 1 was produced.

[0042] Examples 2 to 7 Except for adjusting the gap between the two rolls to achieve the desired weight per unit area and density, the positive and negative electrodes were produced in the same manner as in Example 1. Then, except for attaching a restraining member so as to achieve the restraining pressure shown in Table 1, the batteries of Examples 2 to 7 were produced in the same manner as in Example 1.

[0043] Comparative Examples 1 to 7 Positive and negative electrodes were produced in the same manner as in Example 1, except that the facing capacity ratio was adjusted to the value shown in Table 1 and the gap between the two rolls was adjusted to the desired basis weight and density. Then, the batteries of Comparative Examples 1 to 7 were produced in the same manner as in Example 1, except that a restraining member was attached so as to achieve the restraining pressure shown in Table 1.

[0044] [Table 1]

[0045] 《Reference examples 1~5》 A positive electrode and a negative electrode were manufactured in the same manner as in Example 1, except that the gap between the two rolls was adjusted to achieve the desired weight and density. Then, the batteries of Reference Examples 1 to 5 were manufactured in the same manner as in Example 1, except that a binding member was attached to achieve the binding pressure shown in Table 1. Note that these Reference Examples have the same configuration as conventionally used batteries, and are batteries with lower electrode weights and lower capacities than the above-mentioned Examples and Comparative Examples.

[0046] <Evaluation> (Capacity maintenance rate) The initial charge and discharge were carried out under the following conditions. Note that "CC" stands for constant current method, and "CCCV" stands for constant current-constant voltage method. Also, "C" is the unit of current rate. "1C" stands for the current rate at which the state of charge (SOC) reaches 0-100% after one hour of charging.

[0047] [conditions] (i) Rest: 60 minutes, (ii) CCCV charging: current = 1 / 3C, voltage = 3.8V, final current = 1 / 100C, (iii) Rest: 10 minutes, (iv) CC discharging: current = 1 / 3C, voltage = 2.5V, (v) Rest: 10 minutes After the initial charge and discharge, a charge and discharge cycle test was carried out under the following conditions, and the capacity after 1 charge and discharge cycle and after 100 cycles was measured. The capacity retention rate was measured by dividing the capacity after 100 cycles by the capacity after 1 cycle. The results are shown in Table 1. The capacity after 100 cycles was measured after CCCV charging at a current of 1 / 5C and a voltage of 3.3V, followed by a 10-minute rest.

[0048] [conditions] (i) CCCV charging: current = 1 / 5C, voltage = 4.0V, final current = 1 / 100C, (ii) rest: 10 minutes, (iii) CC discharging: current = 1 / 5C, voltage = 2.5V, (iv) rest: 10 minutes (Gas generation rate) In the above-mentioned charge-discharge cycle test, the amount of gas generated after 1 cycle and the amount of gas generated after 100 cycles were measured based on the volume change obtained by Archimedes' method. The results are shown in Table 1.

[0049] [Table 1]

[0050] <Result> In Examples 1 to 7, the decrease in the capacity retention rate after the cycle test was suppressed and the amount of gas generated was also reduced. On the other hand, in Comparative Examples 1 to 9, the capacity retention rate after the cycle test was lower than in Examples 1 to 7 and the amount of gas generated was larger.

[0051] FIG. 3 is a graph showing the capacity retention rate after the cycle test in Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 5. It was confirmed that the decrease in the capacity retention rate per 10 cycles was suppressed in the battery of Example 3 compared to the batteries of each Comparative Example. In addition, FIG. 4 is a graph showing the amount of gas generation versus the capacity retention rate after the cycle test in the examples and comparative examples. From this result, it was confirmed that the higher the capacity retention rate, the smaller the amount of gas generation.

[0052] In addition, the gas generation amount of each Example was in the range of 2 to 3.8 times compared to each Reference Example. Generally, the gas generation amount is large in the positive electrode, so the basis weight of the positive electrode active material layer can be used as a standard. Since the basis weight of the positive electrode of each Example is about 4.2 times that of each Reference Example, it is considered that the gas generation amount of each Example is reduced from the viewpoint of the basis weight of the positive electrode.

[0053] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]

[0054] 20 positive electrode, 30 negative electrode, 40 separator, 50 electrode body, 90 case, 91 positive electrode terminal, 92 negative electrode terminal, 100 nonaqueous electrolyte secondary battery.

Claims

[Claim 1] A non-aqueous electrolyte secondary battery including an electrode assembly formed by laminating a positive electrode and a negative electrode with a separator interposed therebetween, and an electrolyte solution, The positive electrode includes a positive electrode current collector foil and a positive electrode active material layer, the negative electrode includes a negative electrode current collector foil and a negative electrode active material layer, The weight of the positive electrode active material layer is 28 mg / cm 2 35mg / cm or more 2 is as follows: The density of the positive electrode active material layer is 1.9 g / cm 3 2.1g / cm or more 3 is as follows: The weight of the negative electrode active material layer is 15 mg / cm 2 20mg / cm or more 2 is as follows: The density of the negative electrode active material layer is 1.35 g / cm 3 1.5g / cm or more 3 is less than The electrode body is applied with a confining pressure of 0.2 MPa or more and 0.7 MPa or less in the stacking direction, The positive electrode active material layer contains lithium iron phosphate, The lithium iron phosphate secondary particles have an average particle size of 1 μm or more and 30 μm or less.

Citation Information

Patent Citations

  • Battery pack

    JP2012038530A

  • Lithium ion secondary battery and method for manufacturing the same

    JP2013239375A

  • Positive electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2016058257A

  • Nonaqueous electrolyte secondary battery and manufacturing method thereof

    JP2016081758A

  • Lithium ion secondary battery

    JP2017126484A